Prevalence and Risk Factors of Dengue Fever Among Children in Makassar Indonesia - Santoso, Maya (Generasi Sains Indonesia, 2024)
Dengue fever remains a significant public health concern in tropical regions, particularly in Southeast Asia. This cross-sectional study aimed to assess the prevalence and risk factors of dengue fever among children in Makassar, Indonesia. A total of 400 children aged 0-14 were surveyed, and data were collected on socioeconomic status, environmental conditions, and preventive behaviors such as mosquito net use. The overall prevalence of dengue was 25.8%, with higher rates observed in low-income households and those with standing water. Children from low-income families had a dengue prevalence of 26.8%, while the prevalence in high-income households was 23.5%. Households with standing water had a significantly higher dengue prevalence (30.2%) compared to those without (22.7%). Inconsistent mosquito net use was associated with higher dengue rates, with children in households that sometimes used nets having the highest prevalence (28.3%). These findings highlight the importance of addressing environmental and socioeconomic factors in dengue prevention strategies. Public health efforts should focus on community education, eliminating breeding sites, and promoting consistent use of preventive measures to reduce dengue transmission.